Periodontal status of individuals with Down syndrome: sociodemographic, behavioural and family perception influence - Nuernberg, M. A.A. [UNESP]; Ivanaga, C. A. [UNESP]; Haas, A. N.; Aranega, A. M. [UNESP]; Casarin, R. C.V.; Caminaga, R. M.S. [UNESP]; Garcia, V. G.; Theodoro, L. H. [UNESP] (Wiley, 2019)
Background: The aim of the present study was to assess the periodontal condition of individuals with Down syndrome and the association with sociodemographic and behavioural characteristics and family perception of oral health. Methods: This cross-sectional observational study was performed at a referral centre for dental assistance to disabled persons in Araçatuba, Brazil. Parents of the individuals were interviewed, and the visible plaque index, bleeding on probing, probing pocket depth and clinical attachment level were recorded by one periodontist in six sites per tooth of all teeth. The individual was the unit of analysis. The significance level was set at 5%. Results: Sixty-four subjects (23.8 ± 8.3 years old) were included. Eighteen (28.1%) were diagnosed with gingivitis and 46 (71.9%) with periodontitis. In the multiple logistic regression final model, age and self-reported oral hygiene practices were associated with the occurrence of periodontitis. The chance of having periodontitis was 4.7 times higher among individuals older than 20 years and approximately 4 times higher in patients whose oral hygiene was performed by themselves and their parents, compared with those who performed oral hygiene alone. Sex, follow-up time in the centre, education, degree of participants' dependence, flossing and family history of periodontal disease were not associated with the occurrence of periodontitis. Higher levels of plaque and bleeding were observed for participants with parents reporting bad gingival health (76.2% and 46.9%) and deficient oral hygiene (79.5% and 47.3%). The perception of parents regarding gingival bleeding was correlated with higher bleeding detected clinically (P = 0.01; 50.1%). Conclusions: The prevalence of periodontitis in individuals with Down syndrome is high and increases with age, even in the face of the parents' perception about their children's oral condition.
Keywords: Down syndrome; health promotion; periodontal diseases